Ulū al-Albāb vegetable garden - Mhd. Sarif, Suhaimi; Zainudin, Dolhadi (2020)
This study explores the effect of Ulū al-Albāb Vegetable Garden project in addressing irresponsible consumption with Sustainable Development Goals (SDG) and Rahmatan lil ‘Alamin (RLA). The study proposes that Ulū al-Albāb Vegetable Garden provides living laboratory for advocacy, practice and model for responsible consumption driven by the magnificent notion of Ulū al-Albāb. This study uses qualitative research through participant observation method with the stakeholders of the project. The duration of the study was between July-August 2019. The study found out that Ulū al-Albāb is limited to experiential learning and advocacy of responsible consumption. The factors embedded into Ulū al-Albāb, namely ta’aruf, ta’awun and takaful. Each factor drives Ulū al-Albāb into different levels of achievement with positive impact in responsible consumption experience.